Attitude study towards the mathematics utility in business careers of a private Costa Rica university: Estudio de la actitud hacia la utilidad de la matemática en estudiantes de carreras de administración de una universidad privada costarricense - O., Eduardo Emiliano Muñoz (2019)
This article presents the results of a study about the attitude towards the usefulness of mathematics in students of the careers of the Management area from a private Costa Rican university; whose name remains unrevealed because of a confidentiality agreement. The investigation was conducted in the third quarter of 2016, and was applied to a sample of 847 individuals from a population of 1806 active management students at the time. This study is a product of graduation thesis for the Mathematics Teaching on Technological Environments Program for the Mathematics School of Instituto Tecnológico de Costa Rica. The study objective was to know the level of attitude toward the usefulness of mathematics that students of the administration area from a private Costa Rican university have, as well as the respective relation to the individual’s sex, age and work status. The measurement instrument  "Scale of Attitude towards the Usefulness of Mathematics" by Fennema-Sherman (1976) was used for the study. According to the data obtained, approximately 94.7% of the students showed levels of  "attitude toward the usefulness of mathematic" between medium, high and very high. And from this group, approximately 64.5% indicated levels between high and very high. It can therefore be concluded that, within the sampled students, there is a very good attitude towards the usefulness of mathematics. Statistical evidence was also found of the existence of differences in the variable "attitude towards the usefulness of mathematics" according to the sex of the students participating in the study. On average, men showed higher levels of  "attitude towards the usefulness of mathematics" than women. Regarding the relationship between the attitude towards the usefulness of mathematics and age, five age ranges were defined. These corresponded to: 20 years or less, 21 to 25 years, 26 to 30 years, 31 to 35 years , and 36 years or older. Significant differences were found between at least two of those age ranges. Finally, the study shows evidence of differences in the "attitude towards the usefulness of mathematics between  students with paid employment and those without it. The group corresponding to the students whose jobs are remunerated show higher levels of "attitude toward the usefulness of mathematics than those who do not".